Formulation and Evaluation of O/W Body Cream Containing Patchouli Oil (Pogostemon cablin Benth.) and Drumstick Oil (Moringa oleifera) as Potential Moisturizing Agent - Nadia Isnaini; Vicky Prajaputra; Siti Maryam (Jurnal Penelitian Pendidikan IPA, 2023)
Various compounds and extracts obtained from a wide variety of plants can be employed as natural antioxidants in cosmetics applications. Patchouli oil (Pogostemon cablin Benth.) and drumstick oil (Moringa oleifera) have the ability to fight free radicals and keep skin hydrated, making them excellent candidates for usage as an active component in cosmetic goods like body cream. This research aims to determine the physical quality of a body cream formulation by subjecting it to an accelerated stability test technique for seven cycles. The preparation was evaluated in each cycle, and the results were analyzed using student's t-test. The evaluation results of body cream preparation showed that there was no significant difference (p>0.05) in the preparation during each cycle. As a result, the formulation of the body cream remained stable throughout the storage term of at least six months, which indicates that it can be utilized for an entire year when kept at room temperature. After two weeks of application on dry skin, it was demonstrated that the formulation had the capacity to increase the amount of moisture contained in the skin (from 30% to 60%). In conclusion, the formulation is potentially produced as commercial cosmetic product in the future.